WELLFOCUS PPT: modifying positive psychotherapy for psychosis - Riches, Simon; Schrank, Beate; Rashid, Tayyab; Slade, Mike (American Psychological Association, 2016)
Positive psychotherapy (PPT) is an established psychological intervention initially validated with people experiencing symptoms of depression. PPT is a positive psychology intervention, an academic discipline which has developed somewhat separately from psychotherapy and focuses on amplifying wellbeing rather than ameliorating deficit. The processes targeted in PPT (e.g. strengths, forgiveness, gratitude, savouring) are not emphasised in traditional psychotherapy approaches to psychosis. The goal in modifying PPT is to develop a new clinical approach to helping people experiencing psychosis. An evidence-based theoretical framework was therefore used to modify 14-session standard PPT into a manualised intervention, called WELLFOCUS PPT, which aims to improve wellbeing for people with psychosis. Informed by a systematic review and qualitative research, modification was undertaken in four stages: qualitative study, expert consultation, manualisation and stake-holder review. The resulting WELLFOCUS PPT is a theory-based 11-session manualised group therapy.